A Microenvironment-Sensitive Coumarin-Labeled Peptide for the Assessment of Lipid-Peptide Interactions - Aspee-Lamas, A; Zúñiga-Núñez, D; Barrías-González, P; Mura-Mardones, F (Elsevier Ltd, 2020)
Fluorescent-labeled peptides were synthesized as antimicrobial peptide models for evaluating the peptide interaction with eukaryotic and bacterial lipid membrane models and their dynamics in lipid membrane by fluorescence techniques. In this work, we discuss the behavior of two peptides of 15 residues, C-PEP and PEP (C-PEP being labeled with a coumarin 343) synthesized employing the solid-phase methodology (SPPS). The interaction of these peptides with lipid membranes of different phospholipid composition was studied by steady-state and time-resolved fluorescence spectroscopy, steady-state and time-resolved fluorescence anisotropy and circular dichroism. Both peptides were random coil in an aqueous medium and change their conformation to an α-helix when they were incorporated into DOPC lipid bilayer. In this lipid membrane, the fluorophore-peptide (C-PEP) displayed membrane interaction with a slightly higher partition within the lipid bilayer in comparison with PEP; nevertheless, the secondary structure adopted within the lipid membrane was not significantly modified by the conjugation with the coumarin moiety. In DPPC:DOPC (50:50) liposomes both peptides were less partitioned, as the incorporation was hindered because the lipid membrane is less fluid. And in the liposomes made of POPE:POPG (70:30), a bacterial model lipid membrane, a larger partition constant was observed with the adoption of structures of polyproline II (PPII)-type. The minor conformational disruption as a result of the conjugation with the coumarin moiety would allow modeling the peptide dynamic interaction with membranes using fluorescence techniques. © 2020